2018
DOI: 10.1111/jace.15797
|View full text |Cite
|
Sign up to set email alerts
|

Photo/cathodoluminescence and stability of Gd2O2S:Tb,Pr green phosphor hexagons calcined from layered hydroxide sulfate

Abstract: Hydrothermal reaction at 150°C and pH = 10 for 24 hours crystallized (Gd,RE)2(OH)4SO4 layered hydroxide sulfate (monoclinic structure; RE = Pr, Tb), from which Gd2O2S:RE (hexagonal structure) green phosphor hexagons were derived via facile dehydration in flowing H2 at 1200°C. Rietveld refinement of the XRD patterns yielded cell dimensions that confirmed the direct crystallization of solid solution. Photoluminescence (PL) study at room temperature found absolute quantum yields of ~25.1% and 28.4%, CIE chromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…The ln[( I 0 / I )‐1] vs 1/ kT plot is displayed as the bottom‐left inset in Figure B. Linear fitting of the data yielded a ΔE of ~0.305 eV, which is close to the value (~0.314 eV) reported for the ~10 μm sized (Gd 0.99 Tb 0.01 ) 2 O 2 S hexagons and is remarkably larger than the values of ~0.26 and 0.24 eV determined for the (Gd 0.925 Tb 0.075 ) 2 O 2 S phosphors synthesized via microwave‐assisted solid reaction and traditional high‐temperature solid reaction, respectively . The thermal quenching property of a phosphor is known to be affected by the crystallinity of the host lattice, concentration and spatial distribution of the activator, particle size and size distribution, and the type and content of impurity, which are all associated with the technique and parameters of powder processing.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The ln[( I 0 / I )‐1] vs 1/ kT plot is displayed as the bottom‐left inset in Figure B. Linear fitting of the data yielded a ΔE of ~0.305 eV, which is close to the value (~0.314 eV) reported for the ~10 μm sized (Gd 0.99 Tb 0.01 ) 2 O 2 S hexagons and is remarkably larger than the values of ~0.26 and 0.24 eV determined for the (Gd 0.925 Tb 0.075 ) 2 O 2 S phosphors synthesized via microwave‐assisted solid reaction and traditional high‐temperature solid reaction, respectively . The thermal quenching property of a phosphor is known to be affected by the crystallinity of the host lattice, concentration and spatial distribution of the activator, particle size and size distribution, and the type and content of impurity, which are all associated with the technique and parameters of powder processing.…”
Section: Resultssupporting
confidence: 53%
“…The currently available strategies for LHS synthesis are limited to refluxing a mixed solution of RE sulfate and hexamethylenetetramine and hydrothermal reaction of RE nitrate with ammonium sulfate ((NH 4 ) 2 SO 4 ) . The products are, unfortunately, micron and even tens of micron sized platelike crystals, and/or aggregates of such crystals, from which RE 2 O 2 S of similar morphologies was resulted . It can thus be said that efficient synthesis of RE 2 O 2 S nanopowders of high chemical and phase purity is yet rather challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The history and comparison of common inorganic scintillators is shown in Fig. 1 [11,[86][87][88][117][118][119][120][121][122][123].…”
Section: History and Comparison Of Inorganic Scintillatorsmentioning
confidence: 99%
“…It is also noted in Figure 4b that the emission peaks basically showed same intensity loss rates with increasing temperature (Figure 4b), which indicated that the current DC phosphor cannot be employed as a probe for optical thermometry via fluorescence intensity ratio (FIR) mode. The activation energy (ΔE) of thermal quenching can be calculated from the Arrhenius Equation shown below [31,32]:…”
Section: Lifetime Based Luminescent Thermometry Of Na(gdeu)(wo 4 )mentioning
confidence: 99%